-2(4x-3)+5(2x-1)=

Simple and best practice solution for -2(4x-3)+5(2x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x-3)+5(2x-1)= equation:


Simplifying
-2(4x + -3) + 5(2x + -1) = 0

Reorder the terms:
-2(-3 + 4x) + 5(2x + -1) = 0
(-3 * -2 + 4x * -2) + 5(2x + -1) = 0
(6 + -8x) + 5(2x + -1) = 0

Reorder the terms:
6 + -8x + 5(-1 + 2x) = 0
6 + -8x + (-1 * 5 + 2x * 5) = 0
6 + -8x + (-5 + 10x) = 0

Reorder the terms:
6 + -5 + -8x + 10x = 0

Combine like terms: 6 + -5 = 1
1 + -8x + 10x = 0

Combine like terms: -8x + 10x = 2x
1 + 2x = 0

Solving
1 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 2x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 2x = 0 + -1
2x = 0 + -1

Combine like terms: 0 + -1 = -1
2x = -1

Divide each side by '2'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| y/-8=10 | | 7(x+8)-32= | | -4v+8=5v-10 | | 128-3z/5 | | 4(5x-1)-5(5x-3)= | | 3x-6+6x+12=12x-24 | | 16/72=x/1416 | | -3+6=39 | | 4.9t^2-26t-10=0 | | 6f+2=20 | | -6(3x-5)=19(7-x) | | -6m+3=10-5m | | -2(3x+5)+4(2x+2)= | | 2x^3-10x^2-100x=72 | | 4y-4+y+24=6y-20-4y | | -17=-31-7f | | (268*366)/(4400*156) | | 3-(2x+5)=5+x+2(4-6) | | -104/-8x | | x-9=5x+15 | | (8+4q)(-9)= | | (4x-6)=90and(2x) | | 30-2x+6x+22=90 | | 5-3x=-11+x | | -x+38=2x+17 | | 8(x+4)+10=10x-2(x-5) | | 7.84cm= | | 7.84= | | -2x+14=x+2 | | x^2+7x+36.75=0 | | 3x-2=20-x | | 4-2c=8 |

Equations solver categories